Functional pleiotropism, diversity, and redundancy of Salvia miltiorrhiza Bunge JAZ family proteins in jasmonate-induced tanshinone and phenolic acid biosynthesis. Issue 1 (25th July 2022) - Ma, Pengda; Pei, Tianlin; Lv, Bingbing; Wang, Mei; Dong, Juane; Liang, Zongsuo
Abstract: Jasmonate (JA) signaling regulates plant growth and development, biotic and abiotic stress tolerance, and primary and secondary metabolism biosynthesis. It is extensively modulated by JA-ZIM-domain ( JAZ ) family genes. In previous work, we obtained nine SmJAZ genes of Salvia miltiorrhiza and proved that SmJAZ8 was the core repressor of JA-induced tanshinone and phenolic acid biosynthesis. Here, we demonstrate that SmJAZ3 and SmJAZ4 act as repressors of JA-induced biosynthesis of tanshinones and salvianolic acid B (Sal B). This suggests that SmJAZ3/4 are functionally redundant in tanshinone and Sal B biosynthesis. SmJAZ1/2/5/6/9 are activators of JA-induced tanshinone biosynthesis and repressors of JA-induced Sal B biosynthesis. This demonstrates the redundancy and diversity of SmJAZ1/2/5/6/9 functions. Besides, SmJAZ10 inhibited JA-induced Sal B synthesis, but had no effect on the synthesis of tanshinone. Two-hybrid screening (Y2H) showed that SmJAZs formed homologous or heterogeneous dimers. Y2H and firefly luciferase complementation imaging (LCI) assays revealed that SmJAZs also formed a complex regulatory network with SmMYC2a, SmMYC2b, SmMYB39, and SmPAP1. Quantitative reverse transcription-PCR (qRT-PCR) indicated that SmJAZs regulated each other at the transcriptional level. Herein, we prove that SmJAZ s have functional pleiotropism, diversity, and redundancy in JA-induced tanshinone and phenolic acid biosynthesis. This study provides an important clue for further understanding the inherent biological significance and molecular mechanisms of the JAZ family as the gene number increases during plant evolution.